Action in the City of Padangsidimpuan: Analysis of Fatwa Number 83 of 2023 concerning the Law of Support for the Palestinian Struggle in the Perspective of Maslahah - Muhammad Ridwan (Sekolah Tinggi Agama Islam Az-Zain Sampang, 2024)
The boycott of products is a form of protest or expression of disappointment by the people of Padangsidimpuan against the Israeli residents who are attacking the Palestinian people. This research focuses on analyzing the MUI Fatwa No. 83 of 2023 on the Legal Status of Supporting the Palestinian Struggle from the perspective of al-Ghazali's concept of Maslahah. Interestingly, the MUI Fatwa has consistently served as a fundamental basis for Indonesian Muslims in jihad responses to various international issues, prompting the author to delve deeper into this Fatwa and describe the phenomena occurring around it. This research is qualitative in nature (field research) with a descriptive approach. The results of this study indicate that the product boycott campaign called for by the people of Padangsidimpuan is part of the defense of the Palestinian people against Israel's military aggression. This is in line with MUI Fatwa No. 83 of 2023, which states that it is obligatory to support Palestine as fellow Muslims are in urgent need of assistance (dharurat). Al-Ghazali's Maslahah views that this product boycott can protect the religion and lives of the Palestinian people, in accordance with maslahah daruriyyat. Moreover, this boycott plays a significant role in raising social awareness and Islamic solidarity on global issues, and serves as a diplomatic tool to pressure those involved in oppression, in line with maslahah hajiyyat. Additionally, the product boycott reflects the moral and ethical commitment of the community in supporting justice and human rights, consistent with the concept of maslahah tahsiniyyat.